EUV (Extreme Ultraviolet) oxidized easy-to-clean coating and preparation method and application thereof

By replacing traditional spacer paper with an EUV oxidation easy-to-clean coating, the problems of high cost, complicated operation and pollution of traditional spacer paper are solved, achieving efficient protection and cleaning of glass substrates, and improving production efficiency and product quality.

CN119264755AActive Publication Date: 2025-01-07SICHUAN SHUWANG CHENSHENG NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411476577.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-07
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

In the existing technology, traditional spacer paper has the problems of high cost, complicated operation and possible introduction of pollution while protecting glass substrates. In addition, it is difficult to clean after EUV light irradiation, which affects the cleanliness of glass substrates and production efficiency.

Method used

The coating layer, which is easy to clean and uses EUV oxidation, contains tetrabutyl titanate, photosensitive resin polymer matrix, surfactant, leveling agent and solvent. The coating layer is oxidized and degraded by EUV light irradiation, making it easy to clean and replacing traditional spacer paper for isolation and protection.

Benefits of technology

It effectively protects the glass substrate, reduces production costs, simplifies operation, avoids contamination, and rapidly oxidizes under EUV light and is easy to clean, thereby improving production efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005096277630000051
    Figure BDA0005096277630000051
Patent Text Reader

Abstract

The invention discloses an EUV oxidation easy-to-clean coating layer as well as a preparation method and application thereof, and relates to the technical field of glass production. According to the technical scheme, the photosensitive coating comprises the following components in percentage by mass: 5-15% of tetrabutyl titanate, 10-20% of a photosensitive resin polymer matrix, 1-3% of a surfactant, 2-5% of a flatting agent, 2-5% of a defoaming agent and 65-80% of a solvent. The coating layer can replace traditional spacer paper, effectively protects the surface of the glass substrate, can be rapidly oxidized and degraded under EUV light irradiation, is easy to clean, and achieves a convenient and residue-free cleaning effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass production, and in particular to an EUV oxidation easy-to-clean coating layer and a preparation method and application thereof. Background Art

[0002] In the production process of display devices such as TFT-LCD, glass substrates are key raw materials, and their quality directly affects the performance and yield of the final product. Therefore, it is crucial to take effective protection measures during the transportation, storage and processing of glass substrates. These measures are aimed at preventing quality problems such as scratches and contamination on the surface of the glass substrates and ensuring the smooth progress of the production process.

[0003] At present, in order to isolate the glass substrates and avoid direct contact between the glass substrates, spacer paper is generally used as an isolation material in the production process. Although traditional spacer paper can protect TFT glass substrates to a certain extent, it also has many disadvantages: first, the price of spacer paper is relatively high, which increases the production cost; second, when the glass substrate is introduced into the downstream factory process, the spacer paper needs to be removed manually or mechanically, which is more complicated and reduces production efficiency; most importantly, the spacer paper may introduce additional pollution during use, affecting the cleanliness of the glass substrate.

[0004] With the development of display technology, the ARRAY process and CF (color film) process in panel factories have higher and higher requirements for glass substrates. Before these two key processes, the glass substrate needs to be irradiated with EUV to achieve fine patterning. After irradiation, certain contaminants will remain on the surface of the glass substrate, so it must be cleaned. Therefore, on this basis, developing a coating layer that is compatible with the EUV cleaning process and easy to clean has become a new direction for glass substrate packaging. Summary of the invention

[0005] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art and provide an EUV oxidation easy-to-clean coating layer and its preparation method and application, which can replace traditional spacer paper and effectively protect the surface of the glass substrate. At the same time, it can be quickly oxidized and degraded under EUV light irradiation, is easy to clean, and achieves a convenient and residue-free cleaning effect.

[0006] The technical solution of the present invention is:

[0007] In a first aspect, the present invention provides an EUV oxidation easy-to-clean coating layer, comprising the following components in percentage by mass: 5-15% tetrabutyl titanate, 10-20% photosensitive resin polymer matrix, 1-3% surfactant, 2-5% leveling agent, 2-5% defoaming agent and 65-80% solvent.

[0008] Among them, the EUV-sensitive metal compound tetrabutyl titanate and the photosensitive resin polymer matrix can quickly undergo oxidation reaction under EUV light, causing the structure of the coating layer to be destroyed and becoming easy to clean. At the same time, the photosensitive resin polymer matrix can also provide good stability and adhesion for the coating layer, ensuring that the coating layer will not fall off or be damaged during normal use. Additives such as surfactants, leveling agents, and defoamers can improve the stability of the coating solution and the coating effect.

[0009] Preferably, the photosensitive resin polymer matrix is ​​one or more of polymethyl methacrylate, polyvinyl alcohol cycloacetal styryl pyridinium salt resin and polyimide resin.

[0010] Preferably, the surfactant is sodium dodecyl sulfate.

[0011] Preferably, the leveling agent is sodium perfluorononyloxybenzene sulfonate.

[0012] Preferably, the defoaming agent is polyoxypropylene ethylene oxide glycerol.

[0013] Preferably, the solvent is propylene glycol methyl ether acetate.

[0014] In a second aspect, the present invention provides a method for preparing the above EUV oxidation easy-to-clean coating layer, comprising the following steps:

[0015] S1 mixes all components except the solvent and dissolves them in the solvent to form a uniform coating solution;

[0016] S2 uniformly coats the coating solution on the surface of the glass substrate;

[0017] S3 solidifies the coating liquid on the surface of the glass substrate to form a coating layer.

[0018] Preferably, in step S2, the coating liquid is applied by spin coating, spray coating or dip coating.

[0019] Preferably, in step S3, the coating solution is solidified by heating, ultraviolet curing or natural drying.

[0020] In a third aspect, the present invention provides an application of the above-mentioned EUV oxidation easy-to-clean coating layer, wherein the coating layer replaces the spacing paper as the isolation material between glass substrates, and when it needs to be removed, it can be oxidized and degraded by EUV light irradiation and then cleaned.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The coating layer of the present invention can effectively isolate pollutants such as dust and water vapor in the air, protect the surface of the TFT glass substrate, have good protective performance, and can effectively prevent damage to the glass substrate during transportation, storage and processing stages; second, it is compatible with the EUV cleaning process. Under EUV light irradiation, the metal compounds and photosensitive resin polymer matrix in the coating layer are rapidly oxidized, resulting in the destruction of the coating layer structure, which becomes easy to clean and can be completely removed by simple cleaning steps (such as water washing, air blowing, etc.) without the need for complex processes; third, the cost is low, and there is no need to remove the spacer paper manually or mechanically, which is easy to operate, and is conducive to improving production efficiency and reducing production costs. Therefore, the coating layer of the present invention is used to replace the traditional spacer paper for packaging and transportation of TFT glass substrates, which not only reduces the material cost, but also avoids the pollution problem that may be introduced by the spacer paper. At the same time, in the subsequent customer processing process, the coating layer can be rapidly oxidized and become easy to clean under the EUV cleaning process, achieving a fast and residue-free cleaning effect, and improving production efficiency and product quality. DETAILED DESCRIPTION

[0023] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0024] Example 1

[0025] The EUV oxidation easy-to-clean coating layer of this embodiment includes the following components in percentage by mass: 10% tetrabutyl titanate, 13% polymethyl methacrylate, 72% propylene glycol methyl ether acetate, 2% sodium dodecyl sulfate, 2% sodium perfluorononyloxybenzene sulfonate, and 1% polyoxypropylene oxide ethylene glycerol.

[0026] Example 2

[0027] The EUV oxidation easy-to-clean coating layer of this embodiment includes the following components in percentage by mass: 5% tetrabutyl titanate, 13% polymethyl methacrylate, 77% propylene glycol methyl ether acetate, 2% sodium dodecyl sulfate, 2% sodium perfluorononyloxybenzene sulfonate, and 1% polyoxypropylene oxide ethylene glycerol.

[0028] Example 3

[0029] The EUV oxidation easy-to-clean coating layer of this embodiment includes the following components in percentage by mass: 15% tetrabutyl titanate, 13% polymethyl methacrylate, 67% propylene glycol methyl ether acetate, 2% sodium dodecyl sulfate, 2% sodium perfluorononyloxybenzene sulfonate, and 1% polyoxypropylene oxide ethylene glycerol.

[0030] Example 4

[0031] The EUV oxidation easy-to-clean coating layer of this embodiment includes the following components in percentage by mass: 10% tetrabutyl titanate, 13% polyvinyl alcohol cycloacetal styryl pyridinium salt resin, 72% propylene glycol methyl ether acetate, 2% sodium dodecyl sulfate, 2% sodium perfluorononyloxybenzene sulfonate, and 1% polyoxypropylene oxide ethylene glycerol.

[0032] Example 5

[0033] The EUV oxidation easy-to-clean coating layer of this embodiment includes the following components in percentage by mass: 10% tetrabutyl titanate, 13% polyimide resin, 72% propylene glycol methyl ether acetate, 2% sodium dodecyl sulfate, 2% sodium perfluorononyloxybenzene sulfonate, and 1% polyoxypropylene oxide ethylene glycerol.

[0034] The method for preparing the coating layer of Examples 1-5 comprises the following steps:

[0035] S1: Mix all components except the solvent at room temperature and dissolve them in the solvent, and stir them thoroughly until a uniform and transparent coating solution is formed; the viscosity of the coating solution at 20°C is 2.5 mPa·s to ensure uniformity and leveling during coating.

[0036] S2 prepares a 10cm×10cm TFT glass substrate after cleaning and drying, ensures that there is no dust, oil or other impurities on the surface, and uses spin coating to evenly coat the coating liquid on the surface of the TFT glass substrate, with a spin coating speed of 221rpm and a spin coating time of 8s.

[0037] S3 places the TFT glass substrate coated with the coating liquid on a heating platform, heats and cures it at 250° C. for 2 minutes, so that the coating liquid forms a uniform and dense coating layer on the surface of the TFT glass substrate, and the coating layer thickness is about 2 μm.

[0038] Comparative Example 1

[0039] Comparative Example 1 uses only polycarbonate (PC) as the coating layer material.

[0040] The preparation of the coating layer includes the following steps:

[0041] S1 dissolves PC in dichloromethane solvent to form a coating solution with a viscosity of 2.5 mPa·s at 20°C.

[0042] S2 uses spin coating to evenly coat the coating liquid on the surface of the TFT glass substrate, with a spin coating speed of 221 rpm and a spin coating time of 8 s.

[0043] S3 places the TFT glass substrate coated with the coating liquid on a heating platform, heats and cures it at 150° C. for 2 minutes, so that the coating liquid forms a uniform and dense coating layer on the surface of the TFT glass substrate, and the coating layer thickness is about 2 μm.

[0044] Comparative Example 2

[0045] In Comparative Example 2, only a polyethylene terephthalate (PET) film containing silver nanoparticles (10%) was used as the coating layer, and the thickness of the coating layer was about 2 μm.

[0046] The coating layer is prepared by directly attaching the film to the surface of the TFT glass substrate.

[0047] Comparative Example 3

[0048] Comparative Example 3 uses conventional spacing paper as the insulating material.

[0049] The method of use is: directly place the spacer paper between the TFT glass substrates to protect and separate the TFT glass substrates.

[0050] The coating layer of Comparative Example 4 includes the following components in percentage by mass: 20% polymethyl methacrylate, 75% propylene glycol methyl ether acetate, 2% sodium p-dodecyl sulfate, 2% sodium p-perfluorononyloxybenzene sulfonate, and 1% polyoxypropylene oxide glycerol.

[0051] The coating layer of Comparative Example 5 includes the following components in percentage by mass: 15% tetrabutyl titanate, 80% propylene glycol methyl ether acetate, 2% sodium dodecyl sulfate, 2% sodium perfluorononyloxybenzene sulfonate, and 1% polyoxypropylene oxide glycerol.

[0052] The coating layers of Examples 1-5 and Comparative Examples 1-5 were tested for performance, and the testing method was as follows:

[0053] Pencil hardness: Take 3 cleaned TFT glass substrates coated with a coating layer in Examples 1-5, Comparative Examples 1-2, and Comparative Examples 4-5, and test the hardness of the coating layer according to the test method of ASTM D3363-22 "Standard test method for determination of thin film hardness by pencil test".

[0054] Coating layer removal rate: Take 3 cleaned TFT glass substrates coated with coating layers in Examples 1-5, Comparative Examples 1-2, and Comparative Examples 4-5, respectively, use a film thickness meter to measure and record the thickness of the coating layers, then place them under EUV light source for 30 seconds, use deionized water to clean, dry, measure the thickness of the coating layers again, and calculate the coating layer removal rate to determine the removal of the coating layer. The calculation formula for the coating layer removal rate is as follows:

[0055]

[0056] The performance test results of the coating layers in Examples 1-5, Comparative Examples 1-2 and Comparative Examples 4-5 are shown in Table 1:

[0057] Table 1 Performance test results of the coating layers in Examples 1-5, Comparative Examples 1-2 and Comparative Examples 4-5

[0058] Test items Pencil hardness Coating layer removal rate (%) Example 1 6H 100% Example 2 5H 100% Example 3 5H 100% Example 4 3H 100% Example 5 4H 100% Comparative Example 1 4H 3.2% Comparative Example 2 2H 21.3% Comparative Example 4 4H 93.6% Comparative Example 5 2H 100%

[0059] It can be seen from Table 1 that:

[0060] The removal rate of the coating layer of Examples 1-3 can all reach 100%, and with the increase of the content of tetrabutyl titanate, the pencil hardness of the coating layer increases first and then decreases. This is because when the content of tetrabutyl titanate is low, tetrabutyl titanate can undergo a certain cross-linking effect with polymethyl methacrylate (PMMA), and this cross-linking effect makes the connection between polymer molecular chains more compact, restricts the movement of molecular chains, and makes the polymer film structure more stable, and the ability to resist external forces is enhanced, thereby improving the hardness of the coating layer. However, when the content of tetrabutyl titanate is too much, tetrabutyl titanate agglomerates, and the agglomerated tetrabutyl titanate forms an uneven dispersion in the coating layer, resulting in defects and stress concentration points. These defects and stress concentration points are easy to become weak links of the coating layer when subjected to external forces, thereby causing the hardness of the coating layer to decrease.

[0061] In Example 4, the photosensitive resin polymer matrix uses polyvinyl alcohol cyclic acetal styryl pyridinium salt resin, and the removal rate of the coating layer can also reach 100%, but the hardness of the coating layer is not as good as that of Example 1. This is because: 1) Molecular structure difference: PMMA in Example 1 has a relatively regular molecular structure, and the arrangement between the molecular chains is relatively tight. This tight arrangement can provide a certain rigidity, so that the hardness after film formation is higher, while the molecular structure of the polyvinyl alcohol cyclic acetal styryl pyridinium salt resin in Example 4 is relatively complex and loose, and the spacing between the molecular chains is larger, resulting in the molecular chains being more easily displaced when subjected to external forces, thereby showing lower hardness; (2) Different cross-linking degrees: PMMA is more likely to form a certain degree of cross-linking structure during the film forming process. Cross-linking can enhance the intermolecular force and improve the hardness and strength of the coating layer. However, due to its structural characteristics, the degree of cross-linking of polyvinyl alcohol cyclic acetal styryl pyridinium salt resin is lower under the same film forming conditions, which reduces the hardness of the coating layer.

[0062] In Example 5, the photosensitive resin polymer matrix adopts polyimide resin, and the removal rate of the coating layer can also reach 100%, but the hardness of the coating layer is not as good as that of Example 1. This is because the PMMA in Example 1 has a relatively simple and regular molecular structure, and the molecular chains are arranged more closely, which can form a relatively strong structure, thereby helping to improve the hardness after film formation; while the molecular structure of the polyimide resin in Example 5 is usually more complex, with some flexible segments or irregular structures, which makes the binding force between molecules relatively weak, and is more easily deformed when subjected to external force, resulting in a decrease in the hardness of the coating layer.

[0063] In addition, in Comparative Example 1, only PC is used as the coating layer material. Although it has good hardness and can effectively protect the surface of the TFT glass substrate from scratches, it lacks EUV sensitivity and cannot be effectively cleaned using EUV light, resulting in difficulty in cleaning the coating layer, which requires manual or mechanical removal. In Comparative Example 2, only a PET film containing a small amount of silver nanoparticles is used as the coating layer. Although the silver nanoparticles have a certain sensitivity to EUV light, the hardness of the PET film and the removal rate of the coating layer are far inferior to the coating layer of the present invention, so there is also a problem of difficulty in cleaning. In Comparative Example 3, traditional spacer paper is used as the isolation material without any coating layer. Although the spacer paper can protect the TFT glass substrate from damage during storage and transportation to a certain extent, it is necessary to remove the spacer paper manually or mechanically when the glass substrate is introduced into the downstream factory process, which is inconvenient to operate. In addition, the spacer paper is mostly disposable and expensive, which not only increases the production cost, but also needs to be processed after being discarded, and cannot be recycled for secondary use, which will also have a certain impact on the environment. Comparative Example 4 does not add tetrabutyl titanate. Although it has good hardness and can effectively protect the surface of the TFT glass substrate from scratches, the lack of tetrabutyl titanate makes the film layer EUV sensitive characteristics low, and it cannot be effectively cleaned by EUV light, resulting in incomplete cleaning of the coating layer. Complete removal requires increased EUV irradiation time, resulting in increased production costs. Comparative Example 5 does not add polymethyl methacrylate. Although the removal rate of the coating layer can reach 100%, the hardness of the film after formation is poor and it cannot effectively protect the surface of the TFT glass substrate from scratches.

Claims

1. EUV oxidation easy-to-clean coating layer, characterized in that: The invention comprises the following components in percentage by mass: 5-15% of tetrabutyl titanate, 10-20% of a photosensitive resin polymer matrix, 1-3% of a surfactant, 2-5% of a leveling agent, 2-5% of a defoaming agent and 65-80% of a solvent.

2. The EUV oxidation easy-to-clean coating layer according to claim 1, characterized in that: The photosensitive resin polymer matrix is ​​one or more of polymethyl methacrylate, polyvinyl alcohol cycloacetal styryl pyridinium salt resin and polyimide resin.

3. The EUV oxidation easy-to-clean coating layer according to claim 1, characterized in that: The surfactant is sodium dodecyl sulfate.

4. The EUV oxidation easy-to-clean coating layer according to claim 1, characterized in that: The leveling agent is sodium perfluorononyloxybenzene sulfonate.

5. The EUV oxidation easy-to-clean coating layer according to claim 1, characterized in that: The defoaming agent is polyoxypropylene oxide ethylene glycerol.

6. The EUV oxidation easy-to-clean coating layer according to claim 1, characterized in that: The solvent is propylene glycol methyl ether acetate.

7. The method for preparing the EUV oxidation easy-to-clean coating layer according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1 mixes all components except the solvent and dissolves them in the solvent to form a uniform coating solution; S2 uniformly coats the coating solution on the surface of the glass substrate; S3 solidifies the coating liquid on the surface of the glass substrate to form a coating layer.

8. The method for preparing the EUV oxidation easy-to-clean coating layer according to claim 1, characterized in that: In step S2, the coating liquid is applied by spin coating, spray coating or dip coating.

9. The method for preparing the EUV oxidation easy-to-clean coating layer according to claim 1, characterized in that: In step S3, the coating solution is cured by heating, ultraviolet curing or natural drying.

10. The use of the EUV oxidation easy-to-clean coating layer according to any one of claims 1 to 6, characterized in that: The coating layer replaces the spacing paper as the isolation material between the glass substrates, and when it needs to be removed, it can be oxidized and degraded by EUV light irradiation and then cleaned.

Citation Information

Patent Citations

  • Alcohol-based glass spraying protective film, preparation method and application

    CN111876034A

  • Resin composition for forming protective film and protective film

    US20190153210A1

  • Composition for forming protective film, method for producing protective film, and laminate

    WO2017006625A1